S&S Rosselle / Siti Shariza lllias ... [et al.] - lllias, Siti Shariza; Azmi, Siti Rohani; Ismail, Norazura; Wan Mat, Wan Hafisah; Nik Abdullah, Nik Siti Hanan
S & S Rosselle was focused in the Rosselle drink. It was located at Lot 3022 Pekan Simpang Kuala, Jln Lebuhraya Sultan Abdul Halim, 05400 Alor Setar, Kedah. This area near to Alor Setar city. The entire infrastructure is proviede by Majlis Perbandaran Kota Setar (MPKS). We choose our business because the number of Malay's entrepreneur in the particular field is too small. We are encouraged to interfere in this business because we want to help our Bumiputera especially Malay in getting the product. We also want to introduce the Rosselle product which popular in Kelantan and Terengganu. In addition, this business also promising a high margin of profit rate. Lastly, we also assume that this business can widely expanded since the business is not popular in the north area. Based on our observation, the target market came from Pekan Simpang Kuala, Kuala Kedah, Tandop, Mergong and others area.